SMALL AND MEDIUM ENTERPRISES (SMES) FACE DIGITAL MARKETING - Aries Kurniawan; Moh Asharudin (Muhammadiyah International Journal of Economics and Business, 2018)
The  patterns of  marketing  in  business have  changed  rapidly.  While in  the past, marketing  was done  solely  through  direct  face-to-face transaction,  the  current  existence of  the  internet  leads to   alternative  options   for   commercial   activities,   including   by   using   a   Smartphone   or  gadget, customers  can have  transactions via  various  applications.  These  applications  also offer a variety of  products,  including  apparels, food,  household  needs as well  as  tertiary  needs. To keep with  the pace,  business actors also change  their marketing  patterns. In  addition  to  advertise and  sell  the products  through  conventional  method,  the internet becomes  the  marketing  media  for  business actors.  Nevertheless,  not all of  them are able to change their  marketing  pattern, especially  SMEs. The  factors of  low  educational  background  and lack  of  knowledge  of  the internet, development, and  technology  are the reasons.  Considering  this condition,  it  is  suggested for  business actors to change their marketing  pattern  according  to  the developments  and  technological  advances in  the community  in  order to survive.